Aislamiento de ácido úsnico y parietina de Caloplaca saxicola Hoffm. - Castro Mandujano y Cols., Olivio (2019)
In the present work there was investigated the Caloplaca saxicola (Hoffm.), gathered near Chinchaycocha's lagoon (Carhuamayo – Cerro de Pasco), to an altitude of 4100 msnm. To 240 grams sample, it surrendered to an extraction acetonic for maceration; one separated diverse components of the extract, using the chromatography in column, with the system chloroform - acetone increasing the quantity of acetone; then, the obtained fractions they purified using chromatographic techniques and recrystallizations Finally, they were elucidated and there decided the structures of the obtained solids, analyzing his spectran of IR, H1NMR, C 13NMR, and MS; these are: usnic acid and parietin.